Cisplatin-mediated activation of glucocorticoid receptor induces platinum resistance via MAST1 - Chaoyun Pan (Nature Portfolio, 2021)
Glucocorticoid receptor (GR) agonists - used in the treatment of solid malignant tumors to reduce inflammation - could potentially affect the anti-tumor activity of chemotherapy. Here, the authors identify a mechanism of cisplatin resistance observed with GR agonist treatment, and show the binding and activation of GR by cisplatin, which leads to MAST1 activation and subsequent MAPK re-activation.